The Influence of Aesthetic Gift-Giving Trends on Adolescents’ Spending Patterns: An Islamic Economic Perspective - Dewi Mayang Sari; Dovi Iwan Musthofa Habibillah (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2026)
This study was conducted to analyze the extent to which the trend of giving aesthetic gifts influences the spending patterns of adolescents in Jombang Village from a sharia economics prespective. In addition, this study aso aims to evaluate whether the consumption behaviour of adolescents and the way they interpret aesthetic gifts is more likely to be directed at tertiary needs or merely the fulfillment of desires. This study uses a quantitative approach with an explanatory research design. Primary data were colected through a structured questionnaire distributed to 212 adolescents as respondents, who were selected using multistage sampling from a total population of 451 adolescents. Data analysis was performed using simple linear regression with the help of IBM SPSS software, supported by classical assumption testing, partial testing (t-test), simultaneous testing (f-test), and coefficient of determination analysis.The results of the anaysis show that the trend of aesthetic gifts has a significant influence on the spending patterns of adolescents. This is evidenced by a t-value of 0,6915 at a significance level of 0,000 (p<0,05) and a positive regression coefficient of 0,770. The coefficient of determination (R2=0,185) shows that the aesthetic gift trend variable explains 18,5% of the variation in adolescent spending patterns, while the rest is influenced by other factors outside the research model. . From a sharia economics perspective, the average value of youth spending patterns of 3,94 reflects relatively good financial management skills, but the average value of aesthetic gift trends of 3,88 shows the strong role of social and emotional needs that fall into the category of tertiary needs or desires. Therefore, the level of conformity of consumption behavior with the principles of balance (tawazun) and moderation (I’tidal) is highly dependent on the ability of adolescents to maintain their spending priorities.